The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1037/pha0000402
|View full text |Cite
|
Sign up to set email alerts
|

Sexual discounting: A systematic review of discounting processes and sexual behavior.

Abstract: Behavioral processes underlying sexual behavior are important for understanding normal human functioning and risk behavior leading to sexually transmitted infections (STIs). This systematic review examines delay and probability discounting in human sexual behavior through synthesis of 50 peer-reviewed, original research articles. Sixteen studies focusing exclusively on monetary delay discounting found small effect size positive correlations with sexual risk behaviors. Eleven studies examined delay or probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 156 publications
(372 reference statements)
1
20
0
2
Order By: Relevance
“…Past community‐level studies showed that the location of freely available condoms robustly controlled whether individuals took them (Amass et al, 1993; Carrigan et al, 1995; Honne & Kleinke, 1990). Prior work using the SDDT or a variant called the Sexual Probability Discounting Task (see review by Johnson et al, 2020) used behavioral economics to provide additional clarity on the role of temporal delays or risk of acquiring an STI as a context for condom acquisition, while Strickland et al (2020) added the impact of financial costs on condom purchasing. Our study is the first to demonstrate the interaction of delays and costs on how participants make choices to forego condoms, and more importantly, whether the decision to forego condoms results in abstinence or unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past community‐level studies showed that the location of freely available condoms robustly controlled whether individuals took them (Amass et al, 1993; Carrigan et al, 1995; Honne & Kleinke, 1990). Prior work using the SDDT or a variant called the Sexual Probability Discounting Task (see review by Johnson et al, 2020) used behavioral economics to provide additional clarity on the role of temporal delays or risk of acquiring an STI as a context for condom acquisition, while Strickland et al (2020) added the impact of financial costs on condom purchasing. Our study is the first to demonstrate the interaction of delays and costs on how participants make choices to forego condoms, and more importantly, whether the decision to forego condoms results in abstinence or unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…We thereby submit that the novel application of a reinforcement pathologies perspective on condom use would provide a substantive advancement to the literature. We note that previous behavioral economic work has demonstrated the role of discounting of (see review by Johnson et al, 2020) and demand for condom availability (e.g., Strickland et al, 2020) in risky sexual decisions, yet we are aware of no study to date that examines the intersection of delay discounting of and demand for condoms within an explicit reinforcement pathologies framework.…”
mentioning
confidence: 93%
“…In this series of experiments, we sought to extend this work by applying behavioral economic methods and theory to understand public health response to the COVID-19 pandemic. This work is positioned within the broader conceptual framework of behavioral economic research reviewed above that demonstrates the impact of behavioral economic variables (e.g., delay, cost, probability, framing) on engagement with health behaviors such as substance use or preventive sexual health (e.g., condom use) [ 31 , 33 , 35 , 37 40 ]. Here, we manipulate these behavioral economic dimensions by adapting them for direct relevance to the COVID-19 pandemic (e.g., the delay to receiving a COVID-19 testing result or cost of that test).…”
Section: Introductionmentioning
confidence: 99%
“…A small, but growing, literature suggests that these kinds of tests of novel or as-yet-unexperienced contexts can nonetheless significantly relate to real-world behavior of interest. For example, in the public health domain, studies on sexual discounting relate to HIV-risk behavior [55, 56] and simulated purchasing of a novel fake ID relate to experienced negative alcohol outcomes in underage drinkers [57]. Moreover, there is evidence that tasks such as hypothetical sexual discounting [58] or hypothetical purchase tasks for drugs [59, 60] significantly predict domain-specific outcomes or behavior beyond general monetary discounting or demand for common commodities.…”
Section: Discussionmentioning
confidence: 99%